Remittances and immigration enforcement - Catalina Amuedo Dorantes; Thitima Puttitanun (IZA Journal of Migration, 2014)
Recent increases in US immigration enforcement at the local and state level may be impacting remittance flows to developing countries by curtailing undocumented immigration, restricting the cyclicality of migration flows and limiting employment opportunities for the undocumented. We examine how the remitting patterns of Mexican migrants in the United States are being impacted by two types of immigration enforcement policies: police-based initiatives, such as 287(g) agreements and Secure Communities, and employment-based programs, as is the case with employment verification mandates. We find that increased enforcement reduces the share of migrants sending money home. However, legal migrants remitting money home increase their money outflows enough to offset any reductions in remittance payments from their undocumented counterparts. As a result, the average dollar amount remitted per Mexican migrant rises in the midst of increased uncertainty, safeguarding remittances as one of the least volatile sources of income in the developing world.
Keywords: 330; Mexikaner; Migranten; Rücküberweisungen; USA